Visual portrayals of obesity in health media: promoting exercise without perpetuating weight bias. Issue 4 (26th June 2015) - Pearl, R. L.; Dovidio, J. F.; Puhl, R. M.
Abstract : Health education campaigns for preventing and reducing obesity often contain weight-stigmatizing visual content, which may have unintended negative health consequences. The goal of the present research was to identify non-stigmatizing visual content for health education materials that can promote exercise among people of diverse weight statuses. An online sample of 483 US women viewed: (i) a woman with obesity portrayed stereotypically; (ii) a woman with obesity exercising; (iii) a woman with obesity portrayed neutrally; or (iv) a lean woman exercising. Race of the models pictured was randomized (White or Black). Participants completed measures of weight bias and exercise behavior and attitudes, and provided information about their weight status. Analysis of covariance revealed that responses to stereotypical and exercise images varied by participant weight status. Across participants, neutral obesity portrayals elicited lower expressions of weight-biased attitudes and higher reports of exercise liking/comfort. Among non-overweight participants, images portraying women with obesity stereotypically or counter-stereotypically produced greater endorsement of negative stereotypes than control, lean images. No effects of model race were found. These findings suggest that the public responds differently to visual portrayals of obesity depending on weight status, and neutral portrayals may be an effective route toward promoting exercise without perpetuating stigma.